Capital Rationing and SMEs Profitability in Nigeria - Adurayemi, Adu Cecilia; Ade, Ajigbotoso Moses (International Journal of Sustainability in Research, 2024)
This research paper examined the effect of capital rationing on SMEs profitability in Nigeria. The study discussed the existing literature, empirical review, nature of capital rationing and its implications on investment, and financial performance of SMEs. The paradoxical nature of capital rationing, its challenges and potential use of capital were discussed. The study adopted descriptive research method while findings and recommendations were highlighted.